Privatisation And Entrepreneurship Development In Nigerian Economic Growth - Igbari, Olusola (Advances in Social Sciences Research Journal, 2019)
The fundamental goal for the pursuit of efficient growth; equity; support of entrepreneurship development; alleviation of poverty and environmental protection as well as meeting other needs is seemingly the desire of the Nigerian government and one of its arsenal of actualizing this goal is fund generation through privatization of the public sector. But the reality of the phenomenon has become a conceptual trump card, so politicized that it no longer implies the same meaning it did from the beginning. The study used descriptive method to examine Privatization as a phenomenon and its attendant effects on Entrepreneurship Development vis-à-vis the Nigerian Economic Growth through secondary data collection. It observed the need for the participation of both government and private sector in the development of entrepreneurship which is a key factor to the growth of the nation’s economy. It concludes that the failure of the government in its privatization policies and serious support for small scale industries has contributed to the underdevelopment of the economy. It recommends that government should at all levels establish a strong support and create an enabling environment for small scale industries to thrive.